SPECIALIZED OBJECT-ORIENTED TOOLS FOR THE DEVELOPMENT OF INFORMATIONCALCULATING APPLICATIONS - Arslan Enikeev; Mahfoodh Bilal Ahmed Mohammed (European Scientific Journal, ESJ, 2013)
The paper presents an approach to building specialized objectoriented software tools for the development of so-called informationcalculating applications including computer aided accounting, business correspondence, statistics etc . These software tools form an integrated development environment allowing the computer assisted development of information-calculating applications. This development environment consists of a formula interpreter, a screen form generator and a specialized library of classes. The implementation of all these components was carried out using the Visual FoxPro database system and has been practically tested on a series of commercial applications concerning computer aided accountancy and business correspondence.